Fair Treatment And Organisational Citizenship Behavior in Higher Learning Institutions In Kabale, Uganda - agaba, Moses; Sunday , Arthur; David, Kabagambe Jesse (International Journal of Human Behavior Management, 2026)
This study focused on fair treatment and Organizational Citizenship Behavior within selected higher education institutions in Kabale District,Uganda. There is increasing concern over staff limited cooperation among colleagues, reluctance to take initiative, and low commitment to institutional goals. This study seeks To examine the relationship between fair treatment and Organisational Citizenship Behavior among institutions of higher learning in Kabale District. For the sake of achieving the objective of this study the study adopted a descriptive cross-sectional survey design and also utilized a quantitative approach for data collection, management, and analysis and a sample size of 235 respondents were be drawn from the total study population of 269 individuals. The study's findings revealed that there is a relationship between fair treatment and organizational citizenship behaviour among Kabale District's higher education institutions. The study concluded that there is relationship between fair treatment and Organisational Citizenship Behavior among institutions of higher learning in Kabale District,. The study recommends that Institutions of higher learning in Kabale District should develop and implement clear policies and practices that promote fairness in treatment across all levels of staff,Institutions of higher learning in Kabale District